Collecting the new : museums and contemporary art - Altshuler, Bruce (Princeton, N.J. ; Woodstock : Princeton University Press, 2007)
- A historical introduction / Bruce Altshuler##- The right to be wrong / Howard N. Fox##- To have and to hold / Robert Storr##- 9 minutes 45 seconds / Jeffrey Weiss##- Breaking down categories : print rooms, drawing departments, and the museum / Christophe Cherix##- Keeping time : on collecting film and video art in the museum / Chrissie Iles and Henriette Huldisch##- Collecting new-media art : just like anything else, only different / Steve Dietz##- Beyond the "authentic-exotic" : collecting contemporary Asian art in the twenty-first century / Vishakha N. Desai##- The unconscious museum : collecting contemporary African art without knowing it / Pamela McClusky##- The accidental tourist : American collections of Latin American art / Gabriel Pérez-Barreiro##- Collecting the art of African-Americans at the Studio Museum in Harlem : positioning the "new" from the perspective of the past / Lowery Stokes Sims##- The challenges of conserving contemporary art / Glenn Wharton.
Originally published: 2005.
Includes bibliographical references and index.
boek